A reduction of licensed origins reveals strain-specific replication dynamics in mice - Kawabata, Tsuyoshi (2011)
Replication origin licensing builds a fundamental basis for DNA replication in all eukaryotes. This occurs during the late M to early G1 phases in which chromatin is licensed by loading of the MCM2-7 complex, an essential component of the replicative helicase. In the following S phase, only a minor fraction of chromatin-bound MCM2-7 complexes are activated to unwind the DNA. Therefore, it is proposed that the vast majority of MCM2-7 complexes license dormant origins that can be used as backups. Consistent with this idea, it has been repeatedly demonstrated that a reduction (~60%) in chromatin-bound MCM2-7 complexes has little effect on the density of active origins. In this study, however, we describe the first exception to this observation. A reduction of licensed origins due to Mcm4(chaos3) homozygosity reduces active origin density in primary embryonic fibroblasts (MEFs) in a C57BL/6J (B6) background. We found that this is associated with an intrinsically lower level of active origins in this background compared to others. B6 Mcm4(chaos3/chaos3) cells proliferate slowly due to p53-dependent upregulation of p21. In fact, the development of B6 Mcm4(chaos3/chaos3) mice is impaired and a significant fraction of them die at birth. While inactivation of p53 restores proliferation in B6 Mcm4(chaos3/chaos3) MEFs, it paradoxically does not rescue animal lethality. These findings indicate that a reduction of licensed origins may cause a more profound effect on cell types with lower densities of active origins. Moreover, p53 is required for the development of mice that suffer from intrinsic replication stress.